Effect of cengkeh leaves and kayu manis cortex essential oils blend as anti dental plaque - Ardani, Marisya; Pratiwi, Sylvia Utami Tunjung; Hertiani, Triana (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Dental plaque is a mouth cavity health problem related to microbial biofilm, where Streptococcus mutans is predominant. Adding of essential oils blend in mouthwash has been reported to increase the dental plaque inhibitory activity. The essential oils of clove leaves (Syzygium aromaticum (L.) Merr. & Perry) and cinnamon cortex (Cinnamomum burmanniNees ex Bl.), are known as potential antibacterial and antibiofilm towards S. mutans. This research aims were to reveal the influence of blending the clove leaves and cinnamon cortex essential oils in antibacterial and anti biofilm activity against S. mutans and to find out the optimum composition. Antibacterial assay was performed in nutrient broth media, on microplate flat-bottom polystyrene 96 wells. Biofilm formation inhibition and degradation assays were done in BHI + 2 % sucrose on microplate flexible U-bottom PVC 96 wells. Crystal violet1 % was used to stain the biofilm and Optical Density(OD) was measured at λ 595 nm. Simplex Lattice Design formula was used to calculate the blend optimum composition. TLCbioautography and GC-MS assays were done to revealthe active substances. As conclusion, it was proven that blending the clove leaves and cinnamon cortex essential oils increased the antibacterial and biofilm degradation potency, but reduced the biofilm formation inhibitory effect against S. mutans. The optimum composition of the essential oils blend was 27:73 (% v/v). From our results we suggest that the clove leaves and cinnamon cortex essential oil blend used in this study be developed as anti dental plaque.Key words : clove leaves, cinnamon cortex, essential oils blend, Streptococcus mutans